The Hacker Perspective in Human Rights Education within Digital Culture - Lapa, Andrea (2025)
This article presents a participatory and activist action-research project conducted in Brazil by the Federal Universities of Santa Catarina and Bahia, in collaboration with public schools. The systematized and researched experience offers a thoughtful reflection on the integration of Information and Communication Technologies (ICT) in human rights education, presenting it as both a challenge and an opportunity for new possibilities. The proposal merges hacker education with human rights education. The hacker education paradigm emphasizes the value of autonomy, agency, empowerment, authorship, and collective, collaborative production in an openness of sources and know ledges with, for, and through ICT. This paradigm intersects with the human rights education paradigm, particularly in its promotion of the acceptance of otherness and its commitment to democratic coexistence, plurality, and intercultural education. Based on a project carried out between 2018 and 2022 with basic education teachers, this research aimed to analyze the challenges and opportunities presented by the hacker perspective in human rights education in the digital age. The university-school action is analyzed through the collective understanding of the project's participants and presents principles to guide public policies, teacher education, and educational research, including  the importance of research on the margins, the role of public intellectuals, the dismantling of the subject-object distinction, the promotion of non-hierarchical relationships between universities and schools, and the recognition of teachers as researchers.